Teachers’ Questioning Strategies in Classroom Interaction - Andi Khaerun Niza (Universitas Muhammadiyah Barru, 2024)
This research aimed to find out the questioning strategies in teaching EFL classroom. This research employed qualitative research. The participants of this research were two English teachers of SMP NEGERI 40 MAKASSAR. The data of this research were collected by employing audio recording, observation notes, and interview. The result if this research revealed that the teacher used Question-Planning Strategy (ask question relevant to the students, used closed question, used follow-up question, used yes/no question, used display question) and Question-Controlling Strategy (Repeat the question, modified the question, call on students’ name to answer the question) as the strategy to ask the question in EFL classroom interaction. The teachers used the questioning strategy in order to check about students understanding, to attract student’s attention, to recall back students’ memory and as an intermezzo to make the students not feel bored. By seeing to the student’s response, the students give more positive responses (yelled at the same response, answer correctly, enthusiatic when answering and respond the question spontaneously) than negative response (did not give response/ keep silent and give the wrong answer) for the teachers’ questioning. Therefore, the use of questioning strategy in the classroom interaction are very important in order to affect the students’ learning process.